Detection of Fuel Purity Using the TCS3200 Sensor Using the Euclidean Distance Function - Muhamad Daffa Al Fitra; Abdul Fadlil (Buletin Ilmiah Sarjana Teknik Elektro, 2023)
Petroleum is oil produced by nature. It widely consumed by two-wheeled and four-wheeled vehicles. This research was conducted in order to know the RGB value of each fuel oil. This study aims to examine the purity of each fuel oil. Calculations in this study were carried out using the Euclidean Distance function aiming to find accuracy from the similarity of the average value and standard deviation of each fuel oil. In this study, detecting the purity of fuel oil using the TCS3200 sensor using the Arduino Uno as microcontroller and for output using I2C LCD 16x2. Before detecting fuel oil, sensor calibration is carried out for each fuel oil. After performing the calibration, 30 data collected. Data processing was carried out after the data was obtained, a search was carried out for the average and standard deviation of the RGB values for each fuel oil. After obtaining the values of the mean and standard deviation, we recalculate using the Euclidean Distance function because we get the similarity of the values of the mean and standard deviation. In the calculation of the accuracy of the Euclidean Distance function, it is found that the matching value of Pertamax is 25, Pertamax Turbo is 21, and Dexlite is 28. In this calculation, an accuracy of 82% is obtained.